A Case of Trastuzumab-Associated Cardiomyopathy Presenting as an Acute Coronary Syndrome: Acute Trastuzumab Cardiotoxicity. (6th March 2013) - Hidalgo, Sylvana; Albright, Carol A.; Wells, Gretchen L.
Abstract : Trastuzumab is a monoclonal antibody highly effective in the treatment of several cancers, but its use is associated with cardiac toxicity which usually responds to cessation of the drug and/or medical therapy. We present an unusual case of acute cardiac toxicity temporally related to administration of trastuzumab in which the clinical presentation suggested an acute coronary syndrome. Coronary angiography, however, demonstrated minimal epicardial disease, but new wall motion abnormalities. Furthermore, the patient did not respond to withdrawal of the drug or medical therapy for heart failure.